2007
DOI: 10.1541/ieejias.127.1224
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of a Three-Channel Control Architecture for Bilateral Teleoperation with Time Delay

Abstract: This paper presents a novel three-channel control architecture for bilateral teleoperation with/without time delay. In concrete terms, this system has two transmission channels of position and force information from the master side to the slave side and one transmission channel of force information from the slave side to the master side. The master controller of the proposed three-channel teleoperation system does not include a position controller, i.e. only force control is implemented in the master side, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…Here, structural approach means changing of the communication channel between a master robot and a slave robot. Acceleration based three-channel control system is confirmed that it has almost same transmission characteristics of force and position information between a master robot and a slave robot compared to CDOB approach (14) (15) . Threechannel controller utilizes the information of the master force and slave position and force.…”
Section: Introductionmentioning
confidence: 81%
“…Here, structural approach means changing of the communication channel between a master robot and a slave robot. Acceleration based three-channel control system is confirmed that it has almost same transmission characteristics of force and position information between a master robot and a slave robot compared to CDOB approach (14) (15) . Threechannel controller utilizes the information of the master force and slave position and force.…”
Section: Introductionmentioning
confidence: 81%
“…Furthermore, structural approach is also useful to overcome time delay. Acceleration based three-channel control system is confirmed that it has almost same transmission characteristics of force and position information between a master robot and a slave robot compared to CDOB (10) (11) . Three-channel controllers utilize the information of master force and slave position and force.…”
Section: Introductionmentioning
confidence: 82%
“…1. This structure is 3ch architecture [11] with environment estimation based force prediction in master side. In the slave side, the delayed informations of the master are used.…”
Section: A Control Structurementioning
confidence: 99%
“…On the other hand, the four channel (4ch) architecture [8] (involving transmission of two quantities from master to the slave and vice versa) provide better performance than 2ch architecture under no communication delay [9]. This 4ch architecture have been extended to 3ch architecture in [10], [11] and the robustness of these architecture has been analyzed to deal with the time delay [10]. In [12], the wave theory [4] was incorporated in 4ch and 3ch architecture to stabilize the these architectures.…”
Section: Introductionmentioning
confidence: 99%